IMPLEMENTATION OF DIGITAL-BASED CUSTOMS POLICY: THE TAPLINK.CC APPROACH - Anya Citra Kurnia Nanda; Tukiman Tukiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to analyze the implementation of digital-based customs policies through the use of the taplink.cc platform at the Juanda Customs and Excise Supervision and Service Office in Sidoarjo. Digital transformation in customs services is becoming crucial due to the increasing flow of international trade and the demand for effective, transparent, and accountable public services. This study uses a qualitative method with a descriptive approach, through data collection techniques such as interviews, observation, and documentation. Informants were selected using purposive sampling and snowball sampling techniques. The research analysis is based on George C. Edward III's policy implementation model, which includes aspects of communication, resources, disposition, and bureaucratic structure. The results show that the use of taplink.cc has helped improve access to information and facilitate the public in obtaining digital customs services. However, there are still obstacles to optimizing the use of technology, especially in relation to socialization among service users. Therefore, it is necessary to strengthen policy communication and adjust the bureaucratic structure so that the implementation of digital-based customs policies can run more effectively and sustainably.